Determinants of environmental awareness toward the green living behaviour of students: the role of family, university and social environmental factors in Hanoi, Vietnam - Nguyen Huong-An Thi; Osman Zahir; Serrano Joane; Suhandoko Astri Dwi Jayanti; Intaratat Kamolrat (Environmental & Socio-economic Studies)
The environment has been deteriorating, due to global warming, deforestation and pollution which have been happening increasingly often. As a result, green behavior has become increasingly important, and people are more aware of the environment and are conscious of the need to change their behaviour in order to protect the environment. This study investigated the factors influencing green living behaviours of students in Hanoi andd the level of their environmental awareness including family, university, and social environmental related factors. Quantitative research using a purposive sampling technique was undertaken on 1295 students who were studying in eight universities in Hanoi, Vietnam. The data was collected through online surveys which were posted on social media platforms. The data was analysed using PLS SEM (Partial Least Square, Structural Equation Modelling) with the assistance of SmartPLS 4.0.9.2 software. The research results not only disclose which family, university and social environmental factors have positive and direct effects on green living behaviours, but also provide insights into the mediation effects of environmental awareness influencing students’ green living behaviours. University related factors were shown to have the most positive influence on the environmental awareness of the students and their green living behaviours. The practical implications of this research suggest actionable strategies for higher education institutions, families, and society to improve green living behaviour among students.